Preparation, Investigation and the Study of the Effect of Mn(II) Complex of Catechol and 2-Aminopyridine on Seed Germination - F. I. El-Moshaty; R. S. El-Zweay; M. M. El-Ajaily; A. M. Jerboa (E-Journal of Chemistry)
The formation of mixed ligand complex of Mn(II) with catechol (L1) and 2-aminopyridine (L2) was determined by elemental analyses (C, H and N), molar conductance measurement, thermogravimetric analysis, infrared, electronic and electron paramagnetic resonance spectroscopies. The elemental analysis data show the formation of 1:1:1 [M: L1: L2] complex. The molar conductance measurement shows a non-electrolyte nature. The thermogravimetric analysis data of the complex display the existence of hydrated and coordinated water molecules. The infrared spectral data exhibit the coordination sites that are through -OH,-C=N and –NH2 groups. The electronic spectral data display the electronic transitions of the ligands and suggest an octahedral structure for the complex. The electron paramagnetic resonance spectrum of the complex reveals the existence of paramagnetic phenomena and supports its geometrical structure. Seed germination and root length of grass were also assayed under the effect of MnCl2.4H2O, catechol, 2-aminopyridine and its complex. Mn(II) salt was the most effective on germination than its complex which possess the high test effect on root length, while the ligands are the least active of all.